Parity as failure determinants of labor induction in Bangka Belitung - Dina Delvin Anggriani; Lilik Herawati; Ernawati Ernawati (Universitas Airlangga, 2016)
Objectives: to identify factors affecting labor induction failure in Sungailiat General Hospital, District Bangka, Bangka Belitung.Materials and Methods: This is a case control retrospective analytic study. Population of this study was postterm delivering mother at delivery room Sungailiat General Hospital during July 1st, 2012 to July 1st, 2015. Sampling method conducted for case group was total sampling method with labor induction failure as a inclusion criteria, and no data for first trimester ultrasound, didn’t have a routine antenatal care history, and maternal complication as exclusion criterias as many as 78 samples. Whereas, control group was women whose underwent a success labor induction used random sampling method with 1:1 ratio. Data source was from medical records. Data analysis was chi square with 95% confidence interval.Results: From the 78 samples with labor induction, 19,2 % was ≥ 35 years old, 48,7% was primiparas, 62,8% with infant birth weight ≥ 3500 gram, and from 96 samples, 47,5% with ≥ 5 years pregnancy interval. Statistical analysis result showed factors that affecting induction failure were parity (P Value 0,014, odds ratio 2,970), baby’s weight (P Value 0,016, odds ratio 2,631), pregnancy interval (P Value 0,023, odds ratio 2,993), whereas mother’s age did not show significant effect (P Value 0,383, odds ratio 2,278).Conclusion: Parity has a 2,9 times risk to develop induction failure.